Idealistic, realistic, and unrealistic expectations of pharmacological treatment in persons with type 2 diabetes in primary care - Salinas Martínez, Ana María; Juárez Montes, Angélica Gabriela; Ramírez Morado, Yesenia; Cordero Franco, Hid Felizardo; Guzmán de la Garza, Francisco Javier; Hernández Oyervides, Luis Carlos; Núñez Rocha, Georgina Mayela (Frontiers in Public Health, 2023)
Introduction Information on treatment expectations in diabetes is scarce for Mexican and Latino populations. We determined idealistic, realistic, and unrealistic expectations for metformin, insulin, and glyburide in primary care. We also explored the association between sociodemographic attributes, time since diagnosis, and expectations. Methods This was a cross-sectional study conducted during 2020–2022 in governmental primary care centers. We consecutively included persons with type 2 diabetes aged 30–70 years under pharmacological medication (n = 907). Questions were developed using information relevant to expectation constructs. Data were collected by interview. We used descriptive statistics, a test of the difference between two proportions, and multivariate ordinal logistic regression. Results A high percentage of participants would like to have fewer daily pills/injections or the option of temporarily stopping their medication. Realistic expectations ranged from 47% to 70%, and unrealistic expectations from 31 to 65%. More insulin users wished they could take a temporary break (p < 0.05) or would like to be able to change the route of administration (p < 0.001) than metformin users. More persons with diabetes on insulin expected realistic expectations compared to those on metformin or glyburide (p ≤ 0.01). Being able to interrupt medication upon reaching the glucose goal was higher in combined therapy users (p < 0.001). Conclusion Time since diagnosis, place of residence, sex, and diabetes education were factors associated to expectations. Management of expectations must be reinforced in primary care persons with type 2 diabetes undergoing pharmacological medication.